2009
DOI: 10.1002/jsfa.3759
|View full text |Cite
|
Sign up to set email alerts
|

Screening quality and browning susceptibility of five artichoke cultivars for fresh‐cut processing

Abstract: BACKGROUND: Artichoke is a rich source of bioactive compounds, mainly phenols, in the Mediterranean diet, but its consumption is limited by the complexity of time-consuming trimming operations. Fresh-cut processing would therefore add convenience to its consumption, even though the severity of post-cutting browning of artichoke pieces is still a major problem. Since susceptibility to browning may vary widely among genotypes, the choice of the cultivar is a very critical step in the fresh-cut process. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The higher levels of antioxidant activity in treated samples might be a response of the DPPH reagent to ascorbic acid (Cabezas-Serrano et al, 2009). Nevertheless, samples treated with antioxidant solution maintained significantly higher antioxidant activity (P ≤ 0.05) throughout the storage time (Fig.…”
Section: Total Polyphenol Content and Antioxidant Activitymentioning
confidence: 78%
See 3 more Smart Citations
“…The higher levels of antioxidant activity in treated samples might be a response of the DPPH reagent to ascorbic acid (Cabezas-Serrano et al, 2009). Nevertheless, samples treated with antioxidant solution maintained significantly higher antioxidant activity (P ≤ 0.05) throughout the storage time (Fig.…”
Section: Total Polyphenol Content and Antioxidant Activitymentioning
confidence: 78%
“…The high browning rate of the edible portion, mainly after cutting, restricts the shelf life of fresh-cut heads due to a loss in visual quality (Cabezas-Serrano et al, 2009). Such phenomenon may be prevented by inhibiting the activity of polyphenol oxidase (PPO) enzyme through a proper antibrowning agent (Amodio, Cabezas-Serrano, Peri, & Colelli, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anyway, Veneto genotypes showed a higher ascorbic acid content than others (Cabezas-Serrano, Amodio, Cornacchia, Rinaldi, & Colelli, 2009;Gil-Izquierdo et al, 2001) and this result led us to consider them suitable also for the processing industry. Several studies, in fact, reported the role of ascorbic acid in preventing browning, as found for lettuce (Heimdal, Kuhn, Poll, & Larsen, 1995) and other vegetables (Reyes, Villareal, & Cisneros-Zevallos, 2007), and browning is one of the most important problems of artichoke processing.…”
Section: Resultsmentioning
confidence: 95%